Exploring Factors Influencing Consumer Purchase Intentions at Indomaret Minimarkets in Surakarta City - Nugroho, Basuki; Nany, Magdalena (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The study investigates factors influencing consumer buying interest, focusing on emotions and sentiments. It aims to provide empirical evidence regarding the impact of price, promotion, service quality, products, and location on consumer buying interest at Indomaret stores in Surakarta. The research sampled 150 Indomaret visitors in Surakarta and employs multiple regression analysis to analyze the data. Results indicate that price, promotion, product quality, service quality, and location each individually and collectively significantly influence consumer buying interest.